2013
DOI: 10.4149/bll_2013_121
|View full text |Cite
|
Sign up to set email alerts
|

Importance of systemic mediastinal lymphadenectomy in exact staging of bronchogenic carcinoma

Abstract: Abstract:Background: Constituent part of radical lung resection for lung cancer is a dissection of mediastinal lymph nodes. Lymphadenectomy is a standard procedure in an assessment of clinical stage of the disease. The aim of the study was to map metastasizing of bronchogenic non-small cell lung carcinoma into homolateral mediastinal lymph nodes and to assess the importance of mediastinal lymphadenectomy for exact staging and survival. Results: Tumors in right upper lobe metastasized in 45.5 % into group 1 nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Iatrogenous hemothorax is a distinctive trauma which can occur as a complication of subclavian and jugular cannulation, pleural puncture and lung biopsies or as a complication of cardiothoracic surgery. There were published several reports describing this complication after permanent pacemaker implantation, laparoscopic surgery, transjugular liver biopsy, coronary angiography, translumbar aortography, radiofrequency ablation for lung and liver tumors or oesophageal varices sclerotherapy (6)(7)(8)(9).…”
Section: Since 1925mentioning
confidence: 99%
“…Iatrogenous hemothorax is a distinctive trauma which can occur as a complication of subclavian and jugular cannulation, pleural puncture and lung biopsies or as a complication of cardiothoracic surgery. There were published several reports describing this complication after permanent pacemaker implantation, laparoscopic surgery, transjugular liver biopsy, coronary angiography, translumbar aortography, radiofrequency ablation for lung and liver tumors or oesophageal varices sclerotherapy (6)(7)(8)(9).…”
Section: Since 1925mentioning
confidence: 99%
“…The clinical value of a new method of functional lymph node dissection in video-assisted thoracic surgery right non-small cell lung cancer radical resection metastasis was an important prognostic factor in patients with NSCLC; therefore, anatomical lobectomy combined with systematic lymph node dissection was thought to be the standard operative method for lung cancer radical resection (5)(6)(7), not only to avoid residual cancer and reduce tumor recurrence but also to ensure postoperative pathological TNM stage and to guide postoperative adjuvant therapy, which has important significance for improving patient survival (7)(8)(9). However, in clinical practice, we found that there remained some deficiencies in routine systemic lymph node dissection, including large wounds created by lymph node dissection, much oozing of blood from the wound, poor protection of vagus nerve and its pulmonary branches, and a large volume of postoperative thoracic drainage.…”
Section: Original Articlementioning
confidence: 99%
“…The aim of the diagnostics is to determine the histological classifi cation of tumor (typing), malignity degree (grading), the extent of the malignant process (staging) and the performance status with comorbidities (6).…”
Section: Discussionmentioning
confidence: 99%